Making Research Sociological - Mishra, Chaitanya (Dhaulagiri Journal of Sociology and Anthropology, 2010)
Developing a distinctive disciplinary vantage point is crucial to becoming a professional. Thesis writing at the Master's level allows the professional opportunity of thinking and writing independently. For students of Sociology in particular, it is fundamental to recognize that the social is everywhere. There is nothing that is not socially constituted. Further on, a Sociology student should develop the sociological vantage point in order to see how the social is constituted. This the student can do by engaging and ‘dialoguing' with well-known sociological theorists. The student will then be able to think about how and why societies are historically constituted, how and why societies are diverse, internally differentiated and hierarchized and how and why societies transform themselves. They will learn to unravel the relationship between different levels of a society. In addition, they will also learn the significance of the structure even as they visualize historical human agents change the structure. Keywords: Social; Sociological; Sociological Imagination; Thesis Writing; Social Relationship; Institutions DOI: 10.3126/dsaj.v3i0.2779 Dhaulagiri Journal of Sociology and Anthropology Vol.3 2009 1-18